Development of a national pathology training system using digital pathology and SNOMED-CT - Clare McGenity; Alyn Cratchley; Jocelyn Aldridge; Craig Sayers; W. Scott Campbell; Rajesh C. Dash; Adrienne M. Flanagan; Neil Sebire; Alexander Wright; Waseem Akhtar; Darren Treanor (Journal of Pathology Informatics, 2025)
Introduction: Digital pathology is an important resource in modern pathology education, with many examples of large databases of educational cases now available online. However, there remains a lack of standardization in retrieval and categorization of cases for training within and between institutions. Methods: Over 1600 teaching terms applicable to histopathology were developed and mapped to corresponding SNOMED CT terms to create a large directory of teaching cases. This was then integrated as a pre-defined list into a clinical PACS system for a national digital pathology project covering multiple hospitals and pathology training programs. Results: This resource allows easy allocation of teaching term labels to cases with educational value. A substantial catalog of educational cases has been generated already, with ongoing efforts to expand this with cases from routine clinical practice. The catalog is fully searchable by term for use in training and examinations. Conclusions: A large directory of digital pathology teaching cases was developed with associated corresponding SNOMED CT terms. The directory of terms will be shared with other healthcare providers to expand its use and utility.